Cotinine Test in Evaluating Smoking Cessation at the Day of Bariatric Surgery. (September 2020) - Gormsen, J.; Hjørne, F.; Helgstrand, F.
Background and Aims: Smoking increases the risk of postoperative complications after bariatric surgery. Therefore, preoperative smoking cessation is mandatory according to Danish guidelines before elective bariatric surgery. The aim of this study was to investigate if patients scheduled for bariatric surgery continue to smoke on the day of their operation despite recommendations. Materials and Methods: A prospective single-center study including all patients scheduled for bariatric surgery from June to December 2017 at Zealand University Hospital in Denmark. Urine samples were collected on the day of surgery to test for cotinine. During the minimum preoperative period of 3 months, patients were repeatedly informed of the increased risk of complications, that smoking cessation was mandatory, that rescheduling of the surgery was possible if more time to achieve smoking cessation was necessary, and if tested positive on the day of surgery, the operation would be canceled. Results: Of the 71 patients included, 9 patients (13%) were tested positive. After confrontation with the test result, all but 1 patient confessed to smoking. Overall, 6 out of 12 patients (50%) who were actively smoking at the time of referral tested positive, and 2 out of 25 patients (8%) who claimed to have smoked previously tested positive. No patients claiming no smoking history tested positive. Conclusion: Despite information that smoking cessation was mandatory, and the scheduled bariatric operation would be canceled in case of smoking, up to 50% of patients with a history of smoking still smoked on the day of surgery.